2018
DOI: 10.3139/120.111223
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of LM25 aluminum alloy scraps

Abstract: These days, a lot of metal scraps are generated by the automobile industry since the use of vehicles is increasing globally. As the production of automobile increases, the use of aluminum alloys has been increasing in automobile applications. Since the resources for the production of primary aluminum are getting scarce and the production of primary aluminum is highly expensive, production of components using secondary aluminum alloy in the form of scraps is highly essential. The present study deals with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Mehrabian [17] shown experimentally how trapped air bubble can result in breakaway oxidation and illustrated this mechanism impeccably. Ozer [18] and Bhagyanathan [19] studied the recycling efficiency of aluminum cans and showed that oxidation during remelting is the key parameter for improved melt cleanliness.…”
Section: Introductionmentioning
confidence: 99%
“…Mehrabian [17] shown experimentally how trapped air bubble can result in breakaway oxidation and illustrated this mechanism impeccably. Ozer [18] and Bhagyanathan [19] studied the recycling efficiency of aluminum cans and showed that oxidation during remelting is the key parameter for improved melt cleanliness.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Si-Mg cast alloys are widely used in the automotive industry due to their good castability, high strength/weight ratio, and corrosion resistance [1][2][3]. The microstructure and mechanical properties of these alloys depend on many parameters such as chemical composition, melting, casting, and solidification conditions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, Ni-containing alloy does not contribute significantly to the mechanical properties because it shows brittle properties in new phases such as Al 9 FeNi formed in the system [2]. Since nickel is an expensive alloying element, it is essential to determine the amount of Ni added to the alloy for good performance [3,8]. One way to improve the mechanical properties of Al-Si-Mg alloys at room temperature is ageing (T6) heat treatment.…”
Section: Introductionmentioning
confidence: 99%